Business process re-engineering: The technique to improve delivering speed of service industry in Tanzania - Sungau, Joseph; Ndunguru, Philibert C.; Kimeme, Joseph (INDEPENDENT JOURNAL OF MANAGEMENT & PRODUCTION (IJM&P), 2024)
Nil